2014
DOI: 10.1094/pdis-03-13-0288-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Wheat mosaic virus Infecting Wheat in Western Australia

Abstract: In eastern Australia, there have been several as yet unconfirmed reports of Wheat mosaic virus (WMoV) infecting wheat (3). WMoV, previously known as High plains virus (HPV), is transmitted by the wheat curl mite (WCM, Aceria tosichella). It is often found in mixed infections with Wheat streak mosaic virus (WSMV), also transmitted by WCM (2,3). WSMV was first identified in Australia in 2003 (3). In October 2012, stunted wheat plants with severe yellow leaf streaking were common in a field experiment near Corrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Since then, HP disease has been reported from different regions in the United States, Australia, and New Zealand (13)(14)(15)(16)(17)(18). The causal agent of HP disease is transmitted by the wheat curl mite (Aceria tosichella Keifer) (19,20) and was identified as High Plains virus based on double-membrane virus-like particles and a 32-kDa NC protein from partially purified virion preparations (12,21).…”
mentioning
confidence: 99%
“…Since then, HP disease has been reported from different regions in the United States, Australia, and New Zealand (13)(14)(15)(16)(17)(18). The causal agent of HP disease is transmitted by the wheat curl mite (Aceria tosichella Keifer) (19,20) and was identified as High Plains virus based on double-membrane virus-like particles and a 32-kDa NC protein from partially purified virion preparations (12,21).…”
mentioning
confidence: 99%
“…Moreover, if climate warming alters WCM presence and abundance it would consequently increase the risk of virus transmission by WCM. Indeed, in Australia warm temperatures have been shown to support large WCM populations, thereby intensifying the spread of WSMV in cereal crops [ 7 ]. It has also been suggested that climate change is one of the factors responsible for recent spread of WSMV in central Europe via WCM [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spread of the WCM-virus system to cereal producing regions worldwide is of increasing importance. Although cereal growers and researchers have been aware of this mite-virus pathosystem for about seven decades [ 4 ] it continues to cause significant economic impact, both in long-established invasions, such as in North America [ 5 ], and more recently invaded regions like Australia and South America where it has become a new threat to winter cereal production [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The virus (WMoV) causes High Plains disease, first described in maize and wheat in Texas, Kansas, Colorado, Idaho, Nebraska, andUtah in the 1993-1994 growing seasons (Jensen et al, 1996). The reported disease distribution has expanded in recent years to include Oregon and Washington, where it is problematic in sweet corn (Gieck et al, 2007), and Ohio and Australia where disease has been detected (Coutts et al, 2014;Stewart et al, 2013;Stewart et al, 2014). WMoV is transmitted by the wheat leaf curl mite Aceria tosichella Keifer (Seifers et al, 1997).…”
mentioning
confidence: 99%